Prospective Teacher Training Program in Turkey: A Meta Synthesis Study - Osman Tayyar Çelik; Servet Atik (Anı Publishing, 2020)
The aim of this meta-synthesis is to determine the findings of qualitative research on prospective teacher training in Turkey, the aspects of future prospective teacher training programs, and the deep knowledge and insights in them. Fourteen studies dealing with new prospective teacher training program using qualitative methods introduced in Turkey in 2016 were included in this meta-synthesis. As a result of the analyses, four themes were revealed; mentoring, contribution of prospective teacher training to teacher education, activities, evaluation, and problems encountered in the execution of the program. Then, a second level abstraction was performed, and syntheses were made as follows; 1) mentor selection and workload, 2) professional development, 3) program content and planning, 4) school context, and 5) program accountability. These syntheses point out the aspects that need to be focused on in the in the process of prospective teacher training program development.